Translational opportunities of single-cell biology in atherosclerosis. (7th December 2022) - de Winther, Menno P J; Bäck, Magnus; Evans, Paul; Gomez, Delphine; Goncalves, Isabel; Jørgensen, Helle F; Koenen, Rory R; Lutgens, Esther; Norata, Giuseppe Danilo; Osto, Elena; Dib, Lea; Simons, Michael; et al.
Graphical Abstract: Graphical Abstract Single-cell biology is bringing new clinical meaning to patient heterogeneity in many disciplines. Atlases of the cellular building blocks of the human atherosclerotic plaque have so far shown that: (i) cellular identity is overall preserved, albeit overlapping transcriptional programmes are activated; (ii) changes in cellular cluster abundance appear between healthy and diseased vascular states; (iii) renewed evidence emerged for a role of T cells in human cardiovascular disease (CVD); and (iv) macrophage heterogeneity supports targeting inflammation and lipids while sparing protective subsets. Vascular single-cell biology has clear translational implications for CVD in terms of identification of the molecular pathways of disease resistance vs. disease propensity and genetic risk, guidance in designing new therapies, vaccines and repurposing drugs for CVD, the study of the therapy-induced adaptation of plaque and circulating cells in clinical trials, improved modelling of human CVD through the availability of metagenomic data sets, and advances in patient selection and stratification. GMZB, Granzyme B; Lef1, lymphoid enhancer binding factor 1; Prf1 Perforin 1; Trem2, triggering receptor expressed on myeloid cells 2. Abstract: The advent of single-cell biology opens a new chapter for understanding human biological processes and for diagnosing, monitoring, and treating disease. This revolution now reaches the field of cardiovascular disease (CVD). New technologies to interrogate CVD samples at single-cell resolution are allowing the identification of novel cell communities that are important in shaping disease development and direct towards new therapeutic strategies. These approaches have begun to revolutionize atherosclerosis pathology and redraw our understanding of disease development. This review discusses the state-of-the-art of single-cell analysis of atherosclerotic plaques, with a particular focus on human lesions, and presents the current resolution of cellular subpopulations and their heterogeneity and plasticity in relation to clinically relevant features. Opportunities and pitfalls of current technologies as well as the clinical impact of single-cell technologies in CVD patient care are highlighted, advocating for multidisciplinary and international collaborative efforts to join the cellular dots of CVD. Audio Abstract: